URBAN AIR ENVIRONMENTAL HEALTH INDICATORS: A PRELIMINARY SET FOR CITY OF KUALA LUMPUR - Hoon Leh, Oliver Ling; Ahmad, Shaharuddin; Aiyub, Kadaruddin; Mohd Jani, Yaakob (PLANNING MALAYSIA, 2011)
Environmental health as an aspect of concern on healthy environment, involves relationship between environment and human health. It comprises the aspects of human health and diseases that are determined by factors in the environment, as well as the characteristics of environmental conditions which affect the quality of health. Generally, urban ambient air is more polluted than overall atmosphere. It is due to higher concentration of human activities and more rapid urban development in urban areas. Urban areas produced air pollutants with higher rate as compared to less developed areas and natural environment. Furthermore, the atmosphere has always been one of the most convenient places to dispose of unwanted materials, which includes burning activities. It changes the natural combination of gases in the air and causes higher rate of urban air pollution. Besides, the air pollutants are likely to circulate and remain in the urban environment due to the "dust dome" phenomenon. Air pollutants are potentially affecting human health. Epidemiologic and laboratory studies demonstrate that ambient air pollutants contribute to various negative health problems, especially on the respiratory and cardiovascular systems, skin, and eyes. Research was carried out in developing a set of environmental health indicators for urban air. The determination of environmental health for urban air involves the identification of air-related health conditions and air quality. The preliminary indicators were formulated to examine the air environmental health conditions and issues in city of Kuala Lumpur. Environmental health indicators are providing useful information for decision-makers, and helping in generating discussion among people of different backgrounds.